A Large Squamous Cell Carcinoma on the Face Treated with Wide Excision and Defect Closure Using Forehead Flap Reconstruction - Sutedja EK; Yuliasari R; Rizki KA; Sutedja E (Dove Medical Press, 2022)
Eva Krishna Sutedja,1 Renata Yuliasari,1 Kiki Akhmad Rizki,2 Endang Sutedja1 1Department of Dermatology and Venereology, Faculty of Medicine, University of Padjadjaran/Hasan Sadikin General Hospital Bandung, Bandung, West Java, Indonesia; 2Department of Surgery, Faculty of Medicine, University of Padjadjaran/Hasan Sadikin General Hospital Bandung, Bandung, West Java, IndonesiaCorrespondence: Eva Krishna Sutedja, Department of Dermatology and Venereology, Faculty of Medicine, University of Padjadjaran/Hasan Sadikin General Hospital Bandung, Jl. Pasteur 38, Bandung, West Java, Indonesia, 40161, Tel/Fax +62 222032426 ext 3449, Email evakrishna@yahoo.comIntroduction: Squamous cell carcinoma (SCC) is a non-melanoma skin cancer, with a rising worldwide incidence. Wide excision with an intraoperative frozen section decreases its recurrence rate and metastases.Case: We reported an SCC case in a 50-year-old woman with clinical manifestations of a 4 × 6 × 0.3 cm solitary ulcer that easily bled. Dermoscopy and histopathological examination support the diagnosis of SCC. Due to its size, a wide excision was initiated, followed by a frozen section being carried out to determine the cancer cell-free margin. We performed an additional 1 cm margin excision as residual tumor still remained in the margin on the first excision. The forehead interpolation flap reconstruction was performed right after the excision to cover the extensive defects on the cheek, followed by a full-thickness skin graft (FTSG) for the forehead. The patient recovered well without complication within eight weeks post-procedure.Discussion: SCC with a diameter larger than 2 cm is considered as high-risk, and a wide excision is the standard treatment in this condition. However, this may risk incomplete excision, leaving residual tumor and increased recurrence rate. Intraoperative frozen section aids the surgeon to determine tumor margin, thus improving the success rate of therapy by up to 95%. A skin graft on the cheek was avoided due to concerns of wound contraction, which may lead to lower tissue survival rates with poor color and texture matching. Therefore, we preferred a skin flap to increase tissue survival and preserve facial contour as well as skin color. Forehead interpolation flap was carried out as it could cover the large size of the skin defect. The forehead skin as donor was later closed by a FTSG.Conclusion: Wide excision surgery with frozen sections is the best option for managing large SCC while a skin flap is preferred to close defects on the cheek.Keywords: frozen section, forehead flap, squamous cell carcinoma, wide excision